Компетентнісний підхід як чинник професійного становлення майбутнього фахівця в закладі вищої освіти - Біланич Людмила; Bilanych Lyudmila; Біланич Галина; Bilanych Halyna (Видавництво «Код», 2025)
Резюме. У статті компетентнісний підхід схарактеризовано як чинник професійного становлення майбутнього фахівця в системі вищої освіти. Окреслено сутність понять «компетентність», «компетенція», «компетентнісний підхід», «професійна компетентність», «самоосвітня компетентність». Визначено, що застосування компетентнісного підходу в закладах вищої освіти дає студентам змогу не просто накопичувати знання з відповідних дисциплін, а насамперед стимулює творче й креативне їх використання, внаслідок чого випускник закладу вищої освіти, майбутній фахівець, стає неабияк затребуваним і конкурентоспроможним на ринку праці.

Abstract. The article describes the competency-based approach as a factor in the professional development of a future specialist in the higher education system. The essence of the concepts of «competence», «competence», «competence approach», «professional competence», «selfeducational competence» is outlined. It is determined that the use of the competency-based approach in higher education institutions allows students not only to accumulate knowledge in the relevant disciplines, but primarily stimulates their creative and imaginative use, as a result of which a graduate of a higher education institution, a future specialist, becomes quite in demand and competitive in the labor market. It is proven that the competency-based approach is widely used in the process of designing a system of independent work of students, which indicates the development of self-educational competence in students, recognized as one of the key competencies that constitutes a new quality of education. It has been proven that the implementation of a competency-based approach in education means changing the entire pedagogical system, transitioning to a new type of learning and upbringing. Unlike traditional education, this approach aims not only at students acquiring knowledge, skills and abilities in a separate form, but primarily at developing and forming in them the ability to practice, creatively apply the acquired knowledge and experience in various situations, and readiness for successful activity in real life. It is significant that for the formation of professional competence and key competencies in future specialists at the HEI level, the transition to electronic, mobile and pervasive learning is important, that is, it is necessary to improve the professional training of education seekers using modern methods, forms, means and technologies of learning based on ICT, and in the future – on digital technologies. This will allow students to independently navigate a variety of information, form creative non-standard thinking.
Competency approach as a factor of professional formation of a future specialist in a higher educational institution
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: компетентність; компетентнісний підхід; компетентнісно-спрямована освіта; професійна компетентність; самоосвітня компетентність; фахова підготовка